Understanding the Relationship between Faith-based Locus of Control and Academic Self-Efficacy among Muslim Students in Nigeria - Osita Victor Ossai; Amos Nnaemeka Amedu (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
In spite of numerous research reports demonstrating the relationship between locus of control (LOC) and academic self-efficacy (ASE) among Muslim students, studies on how faith-based LOC relates to ASE among Muslim students in Nigeria are scarce. This study employed a correlation survey to examine the relationship between faith-based LOC and ASE among Muslim students in Nigeria. The sample comprised university undergraduates (n=124) [71 females and 53males] aged between 18 and 35 years in the federal universities in South East, Nigeria. A purposive sampling procedure was used to get the sample for the study. The researchers adopted two instruments for this study: A 20 item structured Faith-based external LOC Scale (FBLCS) adapted from Rotter (1966). The second instrument is a five-item General Academic Self Efficacy Scale (GASES) adapted from Braun et al. (2021). The instrument was used in measuring students’ ASE. The data analysis in this study was done using version 29 of IBM SPSS. The relationship between the study variables was established using regression analysis while linear regression (t-test) and Hayes’ PROCESS were used to analyze the hypotheses. Result shows that there is a significant positive relationship between faith-based LOC and ASE among Muslim students in Nigeria. Furthermore, result also shows that there is no significant influence of gender on the relationship between faith-based LOC and ASE among Muslim students in Nigeria. It was recommended that teachers and stakeholders in Islamic Education system should strive to incorporate the faith aspect of their LOC into their curriculum for optimal development.